دراسة سببية لنقص السمع عند البالغين من مراجعي العيادة الأذنية في مشفى الأسد الجامعي في اللاذقية - الرستم محمد; ابراهيم مصطفى; وقاف سامر (Latakia University Journal -Medical Sciences Series, 2019)
يهدف البحث لإجراء مسح لحالات نقص السمع في العيادة الأذنية في مشفى الأسد الجامعي في اللاذقية لتحديد نسبته و التعرف على أسبابه ,تم تحري( 2000) مريض للكشف عن نقص السمع عندهم ,فكانت نسبة انتشار نقص السمع( 38.5%), أي تم تشخيص نقص السمع عند( 770 ) مريضاً, دون وجود اختلافات يعتد بها إحصائيا" بين الجنسين ,ولكن لوحظت هذه الاختلافات ما بين الفئات العمرية و سجل أعلى انتشار في الفئة العمرية ≥ 67 عاما", و كان أكثر أسباب نقص السمع شيوعا" هو السدادة الصملاخية ( 30 % ) , يليها نقص السمع الشيخي ( 28 % ) , و كان نقص السمع ثنائي الجانب في (77.27%) من الحالات , و أحادي الجانب في (22.42%) من الحالات, اما حسب نوع نقص السمع فكانت النتائج :نقص سمع توصيلي( 51.03 %), حسي عصبي( 45.45%) , مختلط (3.5 %) ,و حسب شدة نقص السمع : نقص سمع خفيف (90.50%) , نقص سمع متوسط( 37%) , نقص سمع شديد (10.51%), نقص سمع عميق (1,55 %) . The goal of this research was to perform a survey of hearing impairment cases in the ear, nose, throat clinic at Al-Assad Hospital in Lattakia and identify their ratio and causes. 2000 patients were examined for hearing impairment; it was found out that the prevalence of hearing impairment was 38,5%, so that 770 cases were diagnosed as ones of hearing impairment,with no significant sex differences. But some differences were spotted particularly in age groups exceeding 67 years; the most common hearing impairment was the cerumen impact (30%), prebycusis(28%); bilateral hearing impairment was present in (77.27%), and unilateral was present in (22.42%). According to the type of hearing impairment, the results were as follows:conductive hearing impairment (51.03%), sensorineural type (45.45%), and mixed type (3.5%). However, according to the degree of hearing impairment, the results were as follows: mild (90.50%), moderate (37%), severe (10.51%), and profound (1.55%).